2013
DOI: 10.1007/s00401-013-1168-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing reveals increased DNA methylation in chronic rat epilepsy

Abstract: Epilepsy is a frequent neurological disorder, although onset and progression of seizures remain difficult to predict in affected patients, irrespective of their epileptogenic condition. Previous studies in animal models as well as human epileptic brain tissue revealed a remarkably diverse pattern of gene expression implicating epigenetic changes to contribute to disease progression. Here we mapped for the first time global DNA methylation patterns in chronic epileptic rats and controls. Using methyl-CpG captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
165
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(184 citation statements)
references
References 78 publications
(100 reference statements)
13
165
4
2
Order By: Relevance
“…Although there are studies showing altered DNA methylation of individual genes during the latent period as well as during the chronic phase, large-scale profiling data are not available on epigenome modifications in epileptogenesis (Pitkänen and Lukasiuk 2011;Kobow et al 2013;Kobow and Blümcke 2014). The only data on global changes in DNA methylation in epilepsy come from the work of Kobow et al (2013), who found alterations in DNA methylation patterns in chronically epileptic rats in the pilocarpine model of TLE. There are, however, few "omics" datasets describing alterations in miRNA expression during epileptogenesis (Table 3), indicating that, similar to mRNA, changes in miRNA expression are dynamic and time dependent.…”
Section: Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%
“…Although there are studies showing altered DNA methylation of individual genes during the latent period as well as during the chronic phase, large-scale profiling data are not available on epigenome modifications in epileptogenesis (Pitkänen and Lukasiuk 2011;Kobow et al 2013;Kobow and Blümcke 2014). The only data on global changes in DNA methylation in epilepsy come from the work of Kobow et al (2013), who found alterations in DNA methylation patterns in chronically epileptic rats in the pilocarpine model of TLE. There are, however, few "omics" datasets describing alterations in miRNA expression during epileptogenesis (Table 3), indicating that, similar to mRNA, changes in miRNA expression are dynamic and time dependent.…”
Section: Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%
“…A recent study suggests that ␤ -hydroxybutyrate, the major ketone that is increased in the blood in animals and patients on the UKD, can alter the epigenetic landscape in mammalian cells by inhibiting histone deacetylase ( 65 ). Another study showed that the UKD reversed the major epigenetic modifi cations found in the brains of epileptic rats ( 66 ). While the effect of the KD on tumor epigenetics has yet to be studied directly, evidence warrants further exploration.…”
Section: The Ketogenic Dietmentioning
confidence: 99%
“…Neither study provides direct evidence in this regard, but based on emerging lines of research (1, 2, 7), both strongly indicate that BHB (and by extension, the KD) could influence the epileptic state. In support of this, the KD has recently been shown to affect epigenetic changes in epileptic brain (17) and is also proving useful in patients with neuroinflammation-related epilepsy (18). With respect to neuroprotection, there are indeed many other KD-related mechanisms that likely play a role (3), such as ketone-mediated inhibition of vesicular glutamate release (19).…”
Section: The New Ketone Alphabet Soup: Bhb Hca and Hdacmentioning
confidence: 99%